2017
DOI: 10.12783/dteees/icmed2016/6256
|View full text |Cite
|
Sign up to set email alerts
|

Study on Industry Choice of Chinese Enterprises’ Outward Foreign Direct Investment Based on Industrial Upgrading

Abstract: It's very important for Chinese enterprises to make industry choice of outward foreign direct investment (OFDI) in order to promote industrial upgrading. At first, we put forward benchmarks Chinese enterprises should follow. Through principal component analysis, we find that OFDI of tertiary industry can promote industrial upgrading most obviously, followed by second industry and primary industry. As to the sector level, we find that high-tech and high value-added sector in tertiary industry is relatively back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…These studies have generally found that the technological progress effects of OFDI are heterogeneous across different regions, different industries, and enterprises with different ownership characteristics. As for the industrial structure effect of OFDI, most studies have found that OFDI has played an optimizing role in the home country's industrial structure (Pan and Yuan, 2016, Andreff, 2017, Nie, 2017, Zhao and Ye, 2018) [6][7][8][9]. However, there is no clear consensus regarding the industrial structural effect of OFDI.…”
Section: The Impact Of Ofdi (None Analyzing the Impact Of Ofdi On Thementioning
confidence: 99%
“…These studies have generally found that the technological progress effects of OFDI are heterogeneous across different regions, different industries, and enterprises with different ownership characteristics. As for the industrial structure effect of OFDI, most studies have found that OFDI has played an optimizing role in the home country's industrial structure (Pan and Yuan, 2016, Andreff, 2017, Nie, 2017, Zhao and Ye, 2018) [6][7][8][9]. However, there is no clear consensus regarding the industrial structural effect of OFDI.…”
Section: The Impact Of Ofdi (None Analyzing the Impact Of Ofdi On Thementioning
confidence: 99%